Christmas freak [videorecording (DVD)] - Marlow, Sean; Hagan, Amy; Drumgold, David; Bulos, Gemma; Basila, David; V, Edward Bernier; Strom, Ashley; Booker, Monica; Horttor, Dylan; Garcia, Salvador; Hoge, Leonard; Chan, Cindy; et al. (Gravitas Ventures, 2021)
Imagine it was Xmas every day. It is for Rudy. He is a Xmas freak. He wants to be cool but he has no friends. A magic scarf transforms him into a cool guy. Or so he believes. But Rudy must learn to be himself and stop hiding behind Xmas.